1981
DOI: 10.1542/peds.68.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress in Motor Vehicles: A Problem in Infancy

Abstract: Children have died from heat stress because they have been left in closed automobiles. Changes in the internal temperature of various sized automobiles left in the Brisbane summer sun were examined. With all windows and doors closed, this temperature rose from an ambient level of 36 C to a maximum of 67 C within 15 minutes and remained there until the doors were opened. Slightly lower temperatures were found for light colored sedans and station wagons. However, all readings were significantly above ambient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Every year, 5000 Australian children are left unattended in the car with potentially fatal consequences. 1 There is limited literature on morbidity from vehicular entrapment in Australia and no published cases in Australia of a child surviving prolonged vehicle entrapment at a daytime temperature as high as 35 C. Deaths have occurred in children trapped in cars with an outside temperature of as low as 14 C. 2 A study in Brisbane with outside temperatures of 36.0 C demonstrated an increase of vehicle temperature to 67.0 C within 15 min with core body temperature likely to be >50 C. 3 Children in the Northern Territory are at increased risk of heat stroke because of higher daytime temperatures than other parts of Australia. This risk is likely to increase across the world as average temperatures rise because of the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Every year, 5000 Australian children are left unattended in the car with potentially fatal consequences. 1 There is limited literature on morbidity from vehicular entrapment in Australia and no published cases in Australia of a child surviving prolonged vehicle entrapment at a daytime temperature as high as 35 C. Deaths have occurred in children trapped in cars with an outside temperature of as low as 14 C. 2 A study in Brisbane with outside temperatures of 36.0 C demonstrated an increase of vehicle temperature to 67.0 C within 15 min with core body temperature likely to be >50 C. 3 Children in the Northern Territory are at increased risk of heat stroke because of higher daytime temperatures than other parts of Australia. This risk is likely to increase across the world as average temperatures rise because of the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Deaths have occurred in children trapped in cars with an outside temperature of as low as 14°C 2 . A study in Brisbane with outside temperatures of 36.0°C demonstrated an increase of vehicle temperature to 67.0°C within 15 min with core body temperature likely to be >50°C 3 . Children in the Northern Territory are at increased risk of heat stroke because of higher daytime temperatures than other parts of Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 With an outside ambient temperature of 38.6°C (98.2°F), the interior temperature of a vehicle increases to 51°C to 67°C (124°F-153°F) within 15 minutes of closing the vehicle's doors and windows. 15 Even on days with moderate ambient temperatures (22°C/72°F), the interior temperature of a stationary vehicle may reach 47°C (117°F) within 60 minutes. 16 Our study supports this notion that even moderate climates are dangerous to children left in stationary vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that the interior temperature in a closed, stationary vehicle is significantly higher than the outside temperature 14 . With an outside ambient temperature of 38.6°C (98.2°F), the interior temperature of a vehicle increases to 51°C to 67°C (124°F–153°F) within 15 minutes of closing the vehicle's doors and windows 15 . Even on days with moderate ambient temperatures (22°C/72°F), the interior temperature of a stationary vehicle may reach 47°C (117°F) within 60 minutes 16 .…”
Section: Discussionmentioning
confidence: 99%